THE STRATEGIES ON TEACHING CONVERSATION CLASS AT THE SECOND SEMESTER STUDENTS OF POLITECHNIC SAHID PONDOK CABE JAKARTA - Rini, Nuryadina Augus (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
Teaching English is challenging especially in speaking skill because the learners speak poorly and teachers must work hard to look for the solution in developing their speaking competence. They have to create thestrategies in teaching speaking. Strategy is particular activities used to accomplish an immediate objective. It is about the implementation or activities in teaching learning process. It can be the ways the teachers used in presenting the materials. Making strategies is based on the the materials, and the condition of the class. Every strategies has the role both of the teachers and the learners, it has the principles. The most important of the strategies is how to make the learners involved in the class.         Based on those reason above, researcher should find the strategies in teaching speaking to solve the problems of the learners. The teachers’ strategies used on teaching are very important for the learners in improving their speaking competence.The strategies would influence the learners’ motivation to learn the language, and to solve their speaking problem.Therefore, the researcher would like to adaptate the strategies used in teaching speaking from Douglas Brown, Jeremy Harmer, and Penny Ur             This study is to implement the strategies on teaching speaking competence in conversation class at the second semester students of Polytechnic Sahid Pondok Cabe Jakarta. The purpose of this study is: (1) to observestudents ability to built up communication, (2) to investigate the improvement of students’ speaking ability in conversation class. The total population is 30 students of the secondsemester students at Polytechnic Sahid Jakarta majoring in Hotel and tourism class. There are 6 meetings used to investigate by the researcher. The technique used to get the data is qualitative purpose which taken from the class observation, interview, and role play. The observation result has shown that the weaknesses of the learners when they applied their ideas are lack of some elements of speaking and the oral production is not productive well, so the speaking is not successful. It can be seen from the feedback they gave in class trough the topic teachers taught .